2013
DOI: 10.1093/ejcts/ezt425
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of efficacy of dynamic compression system in the correction of typical pectus carinatum

Abstract: This preliminary study demonstrated that the DCS with a pressure-measuring device is a minimal invasive system effective for treatment of PC in patients where the anterior chest wall is still compliant. The control of different pressure measurements could be used as the inclusion criterion as well as a predictive factor for aesthetic results and treatment duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
5

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
2
24
0
5
Order By: Relevance
“…In previous published series of patients with chest wall deformities, 90% had associated postural problems and 23% had scoliosis (7, 8). In most patients, physiotherapy was added to the corrective treatment to optimize the results.…”
Section: Methodsmentioning
confidence: 95%
“…In previous published series of patients with chest wall deformities, 90% had associated postural problems and 23% had scoliosis (7, 8). In most patients, physiotherapy was added to the corrective treatment to optimize the results.…”
Section: Methodsmentioning
confidence: 95%
“…These PCOs all have a similar goal to provide a constant force to the sternal protrusion to correct the deformity. An abundance of PCO literature has shown that this method of treatment is successful (Haje & Bowen, 1992;Kang et al, 2014;Kravarusic et al, 2006; R. T. Lee et al, 2013;Lopez et al, 2013;Martinez-ferro et al, 2016). However, research has yet to quantify the PCO forces acting on this deformity or characterize the stiffness and potential change in stiffness of the protrusion during treatment.…”
Section: Chapter Seven: Discussionmentioning
confidence: 99%
“…Several braces exist that perform the same function; that is to provide a constant force to the Lopez et al, 2013;Martinez-ferro et al, 2008). All braces have similar appearances, containing a bar and pad that lies anteriorly to the torso.…”
Section: Bracing Of Pectus Carinatummentioning
confidence: 99%
See 1 more Smart Citation
“…Pounds per square inch (psi) is used as the unit of measure, and pressure under 2.5 psi was considered safe in order to avoid skin lesions. Subsequent authors have also reported their experience with the use of this device: Lopez et al [48] reported its use in patients with PIC as high as 14 psi, with good results in 61 of 68 cases in 17 months; and Cohee et al [49] created an algorithm designed to determine the chances of the condition being resolved with a non-operative approach. De Beer et al [52] validated the use of PIC to predict the duration of treatment, and Poola et al [51] found that a low PIC at the beginning of treatment was a good prognostic factor.…”
Section: Non-surgical Treatmentsmentioning
confidence: 99%